Principles and guidelines for developing implementation methodology of Customer Relationship Management (CRM) systems - Rababah, Khalid; Mohd, Haslina; Ibrahim, Huda (2012)
The implementation of CRM systems has become very necessary for organizations in order to effectively manage their relationships with the customers.Unfortunately, it has faced various failures in different industries. Besides, the existence of implementation methodologies or frameworks that guide the successful implementation of CRM systems are still lacking. In response to that, this paper aims to critically review the methodologies of the existing implementation of CRM system and to comprehensively suggest a set of principles and guidelines for the successful implementation plan of CRM systems.In accordance, this paper compares three most famous CRM implementation methodologies; CRM-iris methodology, CRM-six sigma methodology, and Jun-Wu methodology. As a result, a set of implementation principles and guidelines are suggested to be taken into consideration in the implementation of CRM systems.These principles and guidelines could be tested empirically in the future for the generalization purposes.